2007
DOI: 10.1038/sj.mp.4001986
|View full text |Cite
|
Sign up to set email alerts
|

Association and linkage of allelic variants of the dopamine transporter gene in ADHD

Abstract: Previously, we had reported a genome-wide scan for attention-deficit/hyperactivity disorder (ADHD) in 102 families with affected sibs of German ancestry; the highest multipoint LOD score of 4.75 was obtained on chromosome 5p13 (parametric HLOD analysis under a dominant model) near the dopamine transporter gene (DAT1). We genotyped 30 single nucleotide polymorphisms (SNPs) in this candidate gene and its 5 0 region in 329 families (including the 102 initial families) with 523 affected offspring. We found that (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 66 publications
2
54
0
1
Order By: Relevance
“…Based on our previous investigation, we decided to specifically reanalyze the two suggestive linkage loci in a stratified sample without the 18 Israeli families. 13 Interestingly, the linkage signal on chromosome 16 increased and passed the provisional significance criteria for linkage, with a LOD score of 3.82. Our further simulations demonstrated that this increase was statistically significant (P = 0.035).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on our previous investigation, we decided to specifically reanalyze the two suggestive linkage loci in a stratified sample without the 18 Israeli families. 13 Interestingly, the linkage signal on chromosome 16 increased and passed the provisional significance criteria for linkage, with a LOD score of 3.82. Our further simulations demonstrated that this increase was statistically significant (P = 0.035).…”
Section: Discussionmentioning
confidence: 97%
“…If there is locus-specific genetic heterogeneity where the allele frequencies of the linked locus are significantly different between countries, it might be advantageous to test for linkage with a stratified sample based on a priori knowledge. 30 Given that we found a certain level of background genetic heterogeneity in the IMAGE sample which was reflected by significant allele frequency differences between the Israeli samples and the rest of the IMAGE samples in our previous investigation of 51 ADHD candidate genes, 13 we repeated the same nonparametric linkage analysis without the 18 Israeli families. As shown in Table 2, the suggestive linkage peak on chromosome 16 increased above the provisional criteria of significant linkage while the peak on chromosome 9 decreased.…”
Section: Genotyping and Data Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genome-wide investigations require no a priori hypotheses related to specific genes, but scan the entire genome in an attempt to identify areas harboring genes that contribute some effect on outcome. Several genome-wide scans have identified regions linked with ADHD risk [7,54], including fine mapping by one group to DAT1 (55). Genome-wide approaches also have potential utility in pharmacogenetic investigations.…”
Section: Genome-wide Investigationsmentioning
confidence: 99%
“…2 Although the substantial heritability of ADHD is documented in numerous family, twin and adoption studies, with estimates up to 80%, genome-wide linkage scans and candidate gene studies have failed to reliably identify ADHD-associated genes. 3 Hebebrand and co-workers 4 reported evidence for a risk haplotype at the dopamine transporter (DAT/SLC6A3) locus based on a linkage scan and subsequent finemapping of chromosome 5p13. A linkage analysis of eight extended families with high density of ADHD using a B50 K single-nucleotide polymorphism (SNP) array-based genotyping assay by our group validated previously reported findings and also revealed several novel susceptibility loci.…”
Section: Introductionmentioning
confidence: 99%